Design of a test rig for grouping tiny particles using wet agglomeration - Syed Muhammad Kamal Alsagoff (2019)
The haze seasons in the ASEAN region is becoming an increasingly worrying trend as it has adverse health consequences on vulnerable groups of people. Multiple methods of haze control were studied, including the efficiency of pre-filters in a HEPA filter system. There are several methods of using agglomeration to improve the efficiency of these filters. In this study, wet agglomeration was studied. Several levels of water vapour expulsion rates were tested to observe its effect on chalk powder as it is passed through a grade G4 pre-filter. It was found that the Setting 6 on the humidifier produced the best results with the particle count not going any higher than the original value before chalk was added. This would possibly lead to a huge reduction in maintenance cost of High Efficiency Particulate Air (HEPA) filters. However, further studies still need to be done to test its viability in the long run and improving its effectiveness with a combination of methods.